Review of D. J. Bartholomew's God of chance - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 1989)
Bartholomew wonders whether God takes chances, or leaves some events in nature to chaos, or permits humans to make their own decisions. His argument merits careful attention because this book is by a professional statistician who is theologically articulate.
God of chance - review
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: chance; chaos; law; order; freedom; determinism; indeterminism; science and religion